ROLE OF ORGANIZATIONAL CULTURE IN ENHANCING EMPLOYEE SATISFACTION: AN ANALYTICAL STUDY IN RAFIDAIN BANK – IRAQ - Ghaith Saadi Mohammed Ali; Fatima Abd Ali Salman; Alaa Hussein Fadhil; Dr. Ahmed Abdullah Amanah (Scholars Digest Publishing, 2023)
This study sheds light on the role and importance of organizational culture in enhancing employee satisfaction for at the level of the Iraqi banking system. As the main objective of study is to focus attention of management of banks in the study community to importance of organizational culture with its dimensions in enhancing satisfaction for its employees. Al-Rafidain Bank, with its branches spread in Kerbala governorate, was chosen as a community for current study. The questionnaire, which numbered (78), was distributed to various branch managers, heads of departments, people's officials, administrative and financial units in bank. Some statistical indicators (descriptive and analytical) available in statistical program (SPSS) were used, to display and analyze results of answers of sample members, and determine nature of the relationship between study variables (organizational culture and employee satisfaction).. The most important finding of study is existence of a correlation and a significant effect between study variables included in first and second main hypothesis in order to achieve extent of satisfaction of employee in branches of Rafidain Bank in Holy Kerbala by adopting an organizational culture that touches, considers and conforms to their different societal values, ideas and beliefs.
Keywords: Organizational Culture, Job Satisfaction, Al- Rafidain Bank, Kerbala Governorate- Iraq.